High Sensitivity pH Sensor Based on Porous Silicon (PSi) Extended Gate Field-Effect Transistor - Al-Hardan, Naif H.; Abdul Hamid, Muhammad Azmi; M. Ahmed, Naser; Jalar, Azman; Shamsudin, Roslinda; Kamil Othman, Norinsan; Lim, Kar Keng; Chiu, Weesiong; N. Al-Rawi, Hamzah (MDPI, 2016)
In this study, porous silicon (PSi) was prepared and tested as an extended gate field-effect transistor (EGFET) for pH sensing. The prepared PSi has pore sizes in the range of 500 to 750 nm with a depth of approximately 42 m. The results of testing PSi for hydrogen ion sensing in different pH buffer solutions reveal that the PSi has a sensitivity value of 66 mV/pH that is considered a super Nernstian value. The sensor considers stability to be in the pH range of 2 to 12. The hysteresis values of the prepared PSi sensor were approximately 8.2 and 10.5 mV in the low and high pH loop, respectively. The result of this study reveals a promising application of PSi in the field for detecting hydrogen ions in different solutions.